(untitled) (Physical Education, Health and Social Sciences, 2026)
The current study was carried out to explore the relationship among perceived social support, cultural discrimination and mental health of creative art workers in Pakistan. The data was collected from (N=300) art workers including photographers, musician artists with the age range of … to … by using purposive sampling technique. Multidimensional perceived social support Scale (Zimet et al., 1988; Akhtar et al., 2010), the Everyday Discrimination Scale (Williams & Mohammed, 1997), and a Depression Anxiety Stress Scale (Lovibond & Lovibond, 1995) was used along with demographic information sheet. Data was analyzed using Statistical Package for social Sciences SPSS was used. The result of study revealed that there is significant positive relationship among the social support and mental health. The result also indicated that cultural discrimination is also positively correlated with mental health. The result of study also indicated that social support and cultural discrimination is significant predictor of mental health among the art workers. The limitation of the study are discussed below.